2004
DOI: 10.1007/s10158-004-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Substrate regulation of serotonin and dopamine synthesis in Drosophila

Abstract: In Drosophila melanogaster, serotonin (5-hydroxytryptamine, 5-HT) is required for both very early non-neuronal developmental events, and in the CNS as a neurotransmitter to modulate behavior. 5-HT is synthesized, at least in part, by the actions of Drosophila tryptophan-phenylalanine hydroxylase (DTPH), a dual function enzyme that hydroxylates both phenylalanine and tryptophan. DTPH is expressed in numerous tissues as well as dopaminergic and serotonergic neurons, but it does not necessarily function as both e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…It is not surprising that DTRH tryptophan hydroxylase activity is not inhibited by 5-HT since this is also observed with mammalian Tph2 prepared from rat homogenates (Johansen et al, 1991). The inhibition when assayed with dopamine points to another similarity between DTRH and mammalian tryptophan hydroxylase, and to another difference between the tryptophan hydroxylation of DTRH and that of DTPH, where no inhibition by 5-HT or dopamine is observed (Coleman and Neckameyer, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is not surprising that DTRH tryptophan hydroxylase activity is not inhibited by 5-HT since this is also observed with mammalian Tph2 prepared from rat homogenates (Johansen et al, 1991). The inhibition when assayed with dopamine points to another similarity between DTRH and mammalian tryptophan hydroxylase, and to another difference between the tryptophan hydroxylation of DTRH and that of DTPH, where no inhibition by 5-HT or dopamine is observed (Coleman and Neckameyer, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…DTPH exhibits differential hydroxylase activity based solely on substrate (Coleman and Neckameyer, 2004). When DTPH uses phenylalanine as a substrate, regulatory control is observed that is not seen when tryptophan is used as a substrate.…”
Section: May 2005mentioning
confidence: 88%
“…Behavioral phase state (P-sol) tyrosine synthesis and tryptophan hydroxylase for the synthesis of 5-hydrotryptophan (5-HTP), the precursor of serotonin (17). Except for a small but significant increase in the gregarious head tissue at the fourth stadium, little difference in henna expression was observed between the two phases in investigated tissues or stadia (Fig.…”
Section: Genome-wide Expression Identified the Catecholamine Metabolicmentioning
confidence: 99%
“…Our conclusion thus supports the hypothesis that specific TPH is present in arthropods generally, based on the phylogenetic analysis of the AAAH gene superfamily (Boularand et al 1998;Patton et al 1998). However, whether the PAH in all insects is similar to DTPH (the peripheral TPH in Drosophila) and serves the TPH function (Neckameyer and White 1992;Coleman and Neckameyer 2004) remains unknown. In other words, the question of whether these insects have also compartmentalized the neuronal and peripheral regulation of 5-HT by having two distinct enzymes, each specific for neuronal or peripheral synthesis, is still open.…”
Section: Presence Of Tph In the Brains Of Insectsmentioning
confidence: 99%